Evaluating the Genetic Component of Ischemic Stroke Subtypes: A Family History Study - Jerrard-Dunne, Paula; Cloud, Geoffrey; Hassan, Ahamad; Markus, Hugh S. (Stroke (1970), 2003)
Background and Purpose— Twin and family history studies support a role for genetic factors in stroke risk. Because the etiology of ischemic stroke is heterogeneous, genetic factors may vary by etiologic subtype. We determined the familial aggregation of stroke risk in different stroke phenotypes and used the results to model estimated sample size requirements for case-control studies. Methods— One thousand consecutive white subjects with ischemic stroke and 800 white controls matched for age and sex were recruited. A first-degree family history of stroke and myocardial infarction was obtained by structured interview. Stroke subtype was determined with the use of modified Trial of Org 10172 in Acute Stroke Treatment (TOAST) criteria. Results— A family history of stroke at ≤65 years was a significant risk factor for large-vessel disease (odds ratio [OR], 2.24; 95% CI, 1.49 to 3.36; P <0.001) and for small-vessel disease (OR, 1.93; 95% CI, 1.25 to 2.97; P =0.003). When only cases aged ≤65 years were considered, these ORs increased to 2.93 (95% CI, 1.68 to 5.13) ( P <0.001) and 3.15 (95% CI, 1.81 to 5.50) ( P <0.001), respectively. No significant associations were seen for cardioembolic stroke or stroke of undetermined etiology. Conclusions— A family history of vascular disease is an independent risk factor for both large-vessel atherosclerosis and small-vessel disease, especially in cases presenting before age 65 years. The estimated sample sizes for case-control studies illustrate how candidate gene studies for ischemic stroke might be made more effective by focusing on these specific phenotypes, in which the genetic component of the disease appears to be strongest.